Investigation for Pu-Erh Tea Contamination Caused by Mycotoxins in a Tea Market in Guangzhou - Jin-Yin Wu; Guang-Yu Yang; Jian-Ling Chen; Wen-Xue Li; Jun-Tao Li; Chuan-Xi Fu; Gao-Feng Jiang; Wei Zhu (Journal of Basic & Applied Sciences, 2014)
Objective: The purpose of the present study is to provide raw data for the development of guidelines for tea production and management, as well as relevant health standards. To investigate the mycotoxin contamination in the wet stored Pu-erh tea in a tea market in Guangzhou, we measured the concentrations of aflatoxin B1 (AFB1), fumonisin B1 (FB1), deoxynivalenol (DON), and T-2 toxin in 70 tea samples. Methods: 70 samples of wet stored Pu-erh tea were randomly chosen in the market. Following crushing, brewing, and filtration of the samples, the contaminations of FB1, DON, or T-2 toxin were assayed by ELISA detection kits, and the contamination of AFB1 was measured by the IAC-HPLC method. Results: We found that all tea samples were safe regarding FB1 and T-2 toxin (safety limit, 1 mg/kg and 0.1×10-3mg/kg, respectively). However, 8 out of 70 samples displayed higher AFB1 concentrations compared to the safety limit(5×10-3 mg/kg). Surprisingly, 63 out of 70 samples have exceeded the safety limit for DON (1 mg/kg). Conclusion: Our survey was the first time to find AFB1 and DON contaminations in the wet stored Pu-erh tea in this tea market. Although the FB1 and T-2 toxin in these tea samples has not yet exceeded the safety limits, they were still detectable, which should cause more concern.